An Approach of Ecological Function Zoning in the Direction of Territorial Organization in Thai Binh Province - Anh, Luu The; Thuy, Hoang Luu Thu; Tuan, Tong Phuc (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 2, 2017)
Thai Binh is a coastal province located in the Red River Delta, which is vulnerable to the effects of climate change and sea level rise. However, the formation and intensity of these impacts were varied by characteristics of ecological landscape. Based on the analysis of feature of geology, topography geomorphology and geodynamic, vegetation cover, soils, land, land use and limate change scenarios in Thai Binh province, the author set up the landscape map at scale of 1:50.000 in order to conduct ecological functional zonning. As the result, Thai Binh territory was divided into 3 regions, 7 subregions and 6 ecological functional zones. The result contributed to provide scientific basis for orienting the rational use of the territory in the direction of sustainable development in the context of climate change. Keywords Ecological function, ecological function zonning, Thai Binh  References [1] Bộ Tài nguyên và Môi trường, Kịch bản biến đổi khí hậu và mực nước biển dâng cho Việt Nam, 2016. [2] Sở Tài nguyên và Môi trường Thái Bình. Báo cáo số 301/BC-STNMT ngày 8/12/2016: Tình hình thực hiện nhiệm vụ, kế hoạch năm 2016 và triển khai kế hoạch năm 2017, 2016. [3] Tổng cục Thống kê, Niên giám thống kê năm 2016. Hà Nội, 2016. [4] Qinhua Fang, Luoping Zhang, Huasheng Hong, Liyu Zhang, Frances Bristow, Ecological function zoning for environmental planning at different levels. Environmental Devevelopment Sustainable 10: 41. doi:10.1007/s10668-006-9037-4, (2008), 41. [5] Phạm Quang Anh, Nguyễn An Thịnh, Giáo trình “Cơ sở sinh thái cảnh quan (lý luận và thực tiễn). Trường Đại học Khoa học Tự nhiên, Đại học Quốc gia Hà Nội, 2005. [6] Phạm Hoàng Hải, Nguyễn Thượng Hùng, Nguyễn Ngọc Khánh, Cơ sở cảnh quan học của việc sử dụng hợp lý tài nguyên thiên nhiên, bảo vệ môi trường lãnh thổ Việt Nam. NXB Giáo dục, Hà Nội, 1997. [7] Nguyễn Thế Thôn, Quy hoạch môi trường phát triển bền vững. NXB Khoa học Kỹ thuật, Hà Nội, 2004. [8] Nguyễn Văn Vinh, Một số vấn đề về phân vùng chức năng môi trường áp dụng cho tỉnh Bắc Giang. Tạp chí Địa chính, số 5/2005, (2005) 20. [9] MA, Báo cáo tổng hợp Dự án đánh giá hệ sinh thái thiên niên kỷ (Milliennium Ecosystem Assessment). Viện Địa lý, Hà Nội, 2005. [10] Thomas Greiber and Simone Schiele (Eds.), Governance of Ecosystem Services. Gland, Switzerland: IUCN. Xii + 140 pp, 2011. [11] Đặng Văn Thẩm và nnk,. Thành lập bản đồ cảnh quan tỉnh Thái Bình tỷ lệ 1:50.000. Báo cáo chuyên đề, Viện Địa lý, Hà Nội, 2016. [12] Luật Bảo vệ Môi trường, 2014. [13] UBND tỉnh Thái Bình, Quy hoạch tổng thể phát triển kinh tế xã hội tỉnh Thái Bình đến năm 2020, định hướng đến năm 2030, 2014.